Small-Molecular Drugs for Alzheimer’s Disease - Deng, Yupeng (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Alzheimer’s disease (AD) is predominantly characterized by the accumulation of β-amyloid (Aβ) plaques and the formation of neurofibrillary tangles, which are induced by the hyperphosphorylation of the Tau protein. Furthermore, the pathology of AD extends to include the progressive loss of synapses and neurons, accompanied by reactive gliosis. Mannose sodium capsule is a low molecular weight acidic oligosaccharide compound prepared from Marine brown algae extract. It is an innovative drug independently researched and developed by China with independent intellectual property rights, and has been supported by the national Major Special Project of New Drug Creation and Technology. Among the myriads of pharmacological interventions, Mannatna has emerged as a novel therapeutic agent the drug is the first novel drug targeting the brain-gut axis for the treatment of Alzheimer’s disease in China and the world. Behind its development logic is a new understanding of the pathogenesis of Alzheimer’s disease. that has notably demonstrated both its clinical safety and efficacy in Phase III randomized controlled trials. Post-marketing clinical studies have convincingly corroborated its effectiveness and safety profile across a diverse range of real-world patient populations.